The Static and Dynamic Incidence of Vietnam's Public Safety Net - Van de Walle, Dominique (World Bank, Washington, DC, 2013)
How does Vietnam's public safety net affect outcomes for the poor? Although social welfare programs in Vietnam are centrally mandated, they are locally implemented according to local norms and local poverty standards and often rely heavily on local financing. The author examines the coverage, incidence, and horizontal equity of the programs that can be identified in the data from the Vietnam Living Standards Survey. She looks at the role of location in determining whether the poor are assisted nationally. And she explores dynamic incidence between 1993 and 1998 and the degree to which programs performed a safety net function. The author's analysis shows that coverage and payments to households are low and have had a negligible impact on poverty. In principle, better targeting could improve the impact of current outlays. The analysis also shows that the system was ineffective in protecting households that were vulnerable to shocks. Finally, the results suggest that although there is a greater concentration of poverty-related programs and greater household participation in poorer communes, the system spends more (absolutely and relatively) on the poor in richer communes.